Implementation of the Make A Match Model Assisted by Audio Visual Media to Improve Student Learning Outcomes in Islamic Education Learning at SD Negeri 1706 Papaso II - Harahap, Siti Maryam (Journal of Indonesian Primary School, 2024)
This study aims to improve student learning outcomes in studying Asmaul Husna material by using the Make a Match model combined with an audiovisual learning model. This model was chosen because it can increase student involvement and make it easier for them to understand the concepts in the Asmaul Husna material. This study was conducted in an elementary school with subjects of grade IV students with a total of 22 students, 12 females and 10 males. who have diverse learning abilities. The results of the study indicate that the application of the Make a Match model supported by audiovisual media can improve student motivation, participation, and learning outcomes in the Asmaul Husna material at SDN 1706 Papaso II, Padang Lawas Regency. The Make a Match model is a learning method that invites students to pair up by matching cards or papers that have related information. Students are given cards containing different keywords or concepts, and they must find the right pair of cards based on the information provided. This activity is not only challenging, but also actively involves students in the learning process. In this study, the method used is classroom action research (CAR) with a quantitative approach. Data were collected through observation, learning outcome tests, and interviews to assess the development of students' understanding before and after the implementation of make a match. The results of the study showed that the learning model with the make a match model. showed evidence that it was known that in cycle 1 there were 7 students who had completed learning or around 31.81% while 15 students or 68.18% had not completed it. Then in cycle 2 there was an increase with evidence that children who had completed learning had reached 100% or 15 students in grade IV had all completed it, making cycle 2 the last cycle. The make a match model showed a significant increase in students' understanding of the Asmaul Husna material after using this method in improving students' understanding of the Asmaul Husna material helping students build a better understanding. In addition, students become more active in the learning process and are able to internalize the moral values ​​taught.